Copper chromium catalyst for the production of propylene glycol and acetol from bio-glycerol a plant design - Pena, Rosely D.; Serrano, Edsel John R.; Suyat, Glenn Jansen M. (College of Engineering, University of the Philippines Diliman, 2014)
Propylene glycol is of significant value in today's market. This compound has a broad spectrum of uses with the unsaturated polyester resin comprising the majority of its market segment. As an unsaturated polyester resin, propylene glycol is used in fiberglass-reinforced structure and surface coatings.As an unsaturated polyester resin, propylene glycol is used in fiberglass-reinforced structure and surface coatings. It is also a functional fluid used in antifreeze and deicing solutions, an excellent solvent and extractant, humectant in the pharmaceutical, cosmetic, animal food and tobacco industries and an important ingredient in plasticizers and hydraulic brake fluids.The conventional process for the production of propylene glycol is through the hydrolysis of propylene oxide. Because the method utilizes a petroleum raw material, operates at high conditions and uses excessive water, an alternate route for the production of propylene glycol is proposed. The authors decided to look into the mass production of propylene glycol through the low-pressure hydrogenolysis of glycerol, a process designed by Suppes et. al. High raw material conversion and high product selectivities are obtained using moderate operating conditions. In addition, acetol, a high-value chemical, is produced as an intermediate. The Philippine Biofuels Act encourages the production of biodiesel and thus suggest an abundant supply of the glycerol raw material. This study thus determined the technical and economic feasibility of building a large-scale propylene glycol and actol plant employing the Suppes process in the Philippines.The feasibility study was able to produce a market study for the chemical product and its raw materials. A design basis sheet was provided based on the assessed opportunity provided by the market study. The process flow diagram was also synthesized through applying chemical engineering principles and heuristics. The piping and instrumentation diagram, plant equipment and piping layout was also prepared to be able to understand the process better and is a requirement for the safety study to be accomplished. The safety study includes assignment of alarms, safety trips and interlocks and preparation of a hazard and operability study. A more detailed sizing of static and rotating equipment with due consideration to standards and heuristics was done for more accurate cost estimation. Discounted payback period and internal rate of return.The plant would have an annual capacity of 150,000 MT of propylene glycol and 3,900 MT of acetol. A NPV value of 4.3 B Php after 10 years from the investment analysis performed suggests that the plant is indeed profitable. In addition, a discounted payback period of less than one year makes the project promising to potential investors. The plant was therefore concluded to be technically and economically feasible to operate in the Philippines.